A study of Revised National Tuberculosis Control Programme quality assurance of sputum microscopy at tuberculosis unit - Kumar, Pratik; Lal, Roshan (International Journal of Advances in Medicine, 2019)
Background: Since, Revised National Tuberculosis Control Programme (RNTCP) relies on sputum microscopy for diagnosis, categorization of patients and assessment of treatment, the credibility, success and sustainability of the programme depends on the lab networks. The objectives of this study were to Quality assurance of Sputum Microscopy under RNTCP in Tuberculosis Unit. Methods: A cross-sectional analytic study was conducted at DMC ML Chest hospital, DMC LLRM Hospital and DMC ESI Hospital. On-site evaluation was conducted once a month by Senior Tuberculosis Lab. Supervisor (STLS) of the DMCs (First Controller). This visit included a comprehensive assessment of laboratory safety procedure, conditions of equipment as well as technical components of AFB smear microscopy which includes prepare, staining and reading of smears. This also included examination of five positive and five negative smears in unblinded manner, to observe the quality of smear and staining as well as condition of microscope at each DMCs. A check list prepared for collection and analysis of standard data to point out remedial action. Results: The overall slide positivity rate (SPR) was 20.17% and 23.99% for ZN-stained slides and fluorescence stained slides respectively. On-site evaluation of all DMCs revealed a good result except of DMC- LLR in maintenance of microscope and well organized and clean working areas. The overall concordance for RBRC slides result of ZN-stained slides was 98.64% and overall discordance was 1.35%. The overall agreement in the re-reading of fluorescent stained slides was 100%. The overall sensitivity, specificity, positive predictive value and negative predictive value of blinded re-checked fluorescence stained slides were 100% each respectively. Conclusions: The overall performance of all DMCs is acceptable.